Influence of Pressure on the Temperature Dependence of Quantum Oscillation Phenomena in Semiconductors - G. Gulyamov; U. I. Erkaboev; A. G. Gulyamov (Advances in Condensed Matter Physics)
The influence of pressure on the oscillations of Shubnikov-de Haas (ShdH) and de Haas-van Alphen (dHvA) in semiconductors is studied. Working formula for the calculation of the influence of hydrostatic pressure on the Landau levels of electrons is obtained. The temperature dependence of quantum oscillations for different pressures is determined. The calculation results are compared with experimental data. It is shown that the effect of pressure on the band gap is manifested to oscillations and ShdH and dHvA effects in semiconductors.